Síntese e caracterização elétrica de filmes varistores à base de 'SN''O IND.2' modificados superficialmente por difusão 'CR POT.3+' na região do contorno de grão - Lustosa, Glauco Meireles Mascarenhas Morandi [UNESP] (2014)
The present work was studied obtaining nanoparticles of the system (98,95)SnO2(1,0)ZnO(0,05)Nb2O5 by Pechini method (polymeric precursor method) and the preparation of varistors films of these particles. The powder obtained was characterized by X-Ray Diffraction, Scanning electron microscopy and N2 adsorption. The films of nanoparticles were obtained by deposition on Si (100)/TiO2 (10.000 A°)/Ti (200 A°)/Pt (1500 A°) substrate with 356-406 of thickness, by electrophoretic technique, using stable suspension of this powder. The films were sintered in the microwave oven for temperatures up to 1000 °C and time up to 40 minutes, in order to form and growth of grains. After sintering and characterization SEM, was deposited a layer of Cr3+ ions by electrophoresis on the surface of the film and submitted to heat treatment of 900 and 1000 ° C for 5, 10 and 15 minutes for purposes of diffusion of cations in the grain boundaries. The Cr+3 is responsible for increasing the coefficient of nonlinearity in varistor system based on SnO2, main characteristic required to obtain varistors. This addition allows to control, through the diffusion by heat treatment, the resistivity, breakdown voltage and nonlinearity coefficient in ceramic films based on SnO2 order to use as varistors. After deposition of ions Cr3+ and heat treatment, the films were electrically characterized by analyzing a direct current to the determination of curves V vs I (voltage applied as a function of electrical current) and curves ln(J/T²) vs E1/2, and characterization alternating current (impedance spectroscopy). From the V vs I curves was possible to obtain the coefficient of nonlinearity, breakdown voltage and leakage current. The parameters of the potential barrier formed at grain boundary region were calculated after analysis of the curves ln(J/T²) vs E1/2 obtained by the V vs I measurements as a function of temperature. The films showed nonlinear coefficient (α)...